Repurposing Antidepressants and Phenothiazine Antipsychotics as Efflux Pump Inhibitors in Cancer and Infectious Diseases - Bálint Rácz; Gabriella Spengler (MDPI AG, 2023)
Multidrug resistance (MDR) is a major obstacle in the therapy of infectious diseases and cancer. One of the major mechanisms of MDR is the overexpression of efflux pumps (EPs) that are responsible for extruding antimicrobial and anticancer agents. EPs have additional roles of detoxification that may aid the development of bacterial infection and the progression of cancer. Therefore, targeting EPs may be an attractive strategy to treat bacterial infections and cancer. The development and discovery of a new drug require a long timeline and may come with high development costs. A potential alternative to reduce the time and costs of drug development is to repurpose already existing drugs. Antidepressants and antipsychotic agents are widely used in clinical practice in the treatment of psychiatric disorders and some somatic diseases. Antidepressants and antipsychotics have demonstrated various beneficial activities that may be utilized in the treatment of infections and cancer. This review aims to provide a brief overview of antibacterial and anticancer effects of selective serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants (TCAs) and phenothiazine antipsychotics, while focusing on EPs. However, it should be noted that the antimicrobial activity of a traditionally non-antibiotic drug may have clinical implications regarding dysbiosis and bacterial MDR.